EFEKTIVITAS PENGGUNAAN MEDIA BOLDING TERHADAP KETERAMPILAN MENULIS CERPEN MURID KELAS V SD MUHAMMADIYAH 3 MAKASSAR - Ashara Ramadani, Nadyah; Aliem Bahri; Khadijah Razak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem in this study is the lack of short story writing skills in class V students at Muhammadiyah 3 Makassar Elementary School in Makassar City. So the researcher uses Bolding media (scoling ball). This research aims to find out the effectiveness of the use of bolding media on the short story writing skills of students in class V of Muhammadiyah Elementary School 3 Makassar City. This research uses experimental quantitative methods with One Group Pretest and Posttest Design designs. The population of this study is the entire students of class V of SD Muhamammadiyah 3 Makassar which is 15 people, the sample draw used in this study is using total sampling, which means that the entire population is used as a research sample. The data collection techniques used are through Pretest and Posttest, data is collected through short story writing skills tests. Next, the entire data obtained was analyzed using descriptive statistics and inferential statistics.